2001
DOI: 10.1046/j.1365-2141.2001.03201.x
|View full text |Cite
|
Sign up to set email alerts
|

Homozygosity for the C→T polymorphism at nucleotide 46 in the 5′ untranslated region of the factor XII gene protects from development of acute coronary syndrome

Abstract: Summary. Recently, a C3T polymorphism at nucleotide 46 in the 5H -untranslated region of the factor XII (FXII) gene was shown to be associated with lower levels of FXII. To study the impact of this polymorphism on the development of an acute coronary syndrome (ACS), we compared 303 patients with ACS and 227 patients with stable coronary artery disease (CAD). In the latter group, 54´2% of individuals carried wild-type FXII:46C, 37´9% were heterozygous FXII:C46T and 7´9% were homozygous for FXII:46T. In contrast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
2
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 11 publications
(19 reference statements)
1
30
2
1
Order By: Relevance
“…However, these findings are not in accordance with previous observations of Endler et al [14,15] , who suggested that the presence of the T allele for the 46C ] T polymorphism at F12 could represent a protective factor for CAD considering that this genetic variation is associated with decreased F12 activity [15] . In view of these contradictory results, the aim of the present study was to evaluate the possible association between the 46C ] T gene polymorphism of the F12 gene and CAD in Chilean subjects.…”
Section: Introductioncontrasting
confidence: 56%
See 1 more Smart Citation
“…However, these findings are not in accordance with previous observations of Endler et al [14,15] , who suggested that the presence of the T allele for the 46C ] T polymorphism at F12 could represent a protective factor for CAD considering that this genetic variation is associated with decreased F12 activity [15] . In view of these contradictory results, the aim of the present study was to evaluate the possible association between the 46C ] T gene polymorphism of the F12 gene and CAD in Chilean subjects.…”
Section: Introductioncontrasting
confidence: 56%
“…In several studies [10][11][12][13][14] , the association between the 46C ] T polymorphism of the F12 gene and cardiovascular diseases has been investigated. However, the results are controversial.…”
Section: Discussionmentioning
confidence: 99%
“…If the authors of the letter had cared to check on the publication record of the people involved in our study, they would have realized that the authors of our study have extensive experience with PCR technology and thus are well aware of the differences between PCR and determination of serum cholesterol or CRP. [2][3][4][5][6][7] We also are confident that Stroke, as a high-ranking and prestigious journal of the American Heart Association, carefully selects reviewers who are well experienced in the field of the respective study.…”
Section: Responsementioning
confidence: 99%
“…Also, several studies have failed to find an association between detection of C pneumoniae DNA in atheromas and peripheral blood mononuclear cells. [5][6][7] The conclusions of Prager et al are based on data that are probably biased by poor methodology.…”
Section: To the Editormentioning
confidence: 99%
“…19 -22 The relationship between FXII activity and risk of coronary artery disease is still unclear. [23][24][25] Overall, the significance of abnormal FXII activities, especially FXII deficiency, remains unknown, but it is generally thought to have minimal clinical consequences.…”
mentioning
confidence: 99%